ANALYSIS OF POLICIES OF THE SAMBAS DISTRICT GOVERNMENT IN THE CASE OF COVID-19 AS A HUMAN SECURITY CRISIS - Rulida Yuniarsih; Thamrin Thamrin; Dewi Suratiningsih (Lafadz Jaya Publisher, 2023)
West Kalimantan is one of the provinces with State Cross-Border Posts, namely in Aruk, Sambas district and State Cross-border Posts in Entikong, Sanggau Regency. However, applying policies regarding mobility restrictions and health protocols is considered lax. Thus, the Governor of West Kalimantan instructed the Regent of Sambas to tighten further regulations regarding the handling and prevention of the Covid 19 case to prevent a wider spread and mitigate the following impacts, such as the economic impact. This article aims to analyze the policies set and implemented in Sambas Regency regarding the handling of the Covid 19 case in Sambas Regency and at the State Cross Border Post in Aruk. Researchers used a qualitative descriptive approach with library and field research through in-depth interviews, observation, and documentation.